2023
DOI: 10.1101/2023.04.03.535302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Piezo inhibition preventsandrescues scarring by targeting the adipocyte to fibroblast transition

Abstract: While past studies have suggested that plasticity exists between dermal fibroblasts and adipocytes, it remains unknown whether fat actively contributes to fibrosis in scarring. We show that adipocytes convert to scar-forming fibroblasts in response to Piezo-mediated mechanosensing to drive wound fibrosis. We establish that mechanics alone are sufficient to drive adipocyte-to-fibroblast conversion. By leveraging clonal-lineage-tracing in combination with scRNA-seq, Visium, and CODEX, we define a mechanically na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…(43) The implication of adipocyte-related pathways in the putatively pro-fibrotic myeloid cluster (Fig. 3E) may also be of interest: fat and fibroblasts/fibrosis are increasingly understood to have an intimate relationship; (40,44,45) lipid dysregulation is common at insulin injection sites and often co-occurs with fibrosis;(4-6) and we have previously postulated that, given current knowledge about the relationship between mechanical forces and adipocytes, tension offloading could be beneficial for both fibrosis and lipodystrophy in the setting of insulin use. (2) Conversely, other cell crosstalk pathways enriched in PP skin have been implicated by other studies as involved in tissue repair and/or possibly anti-fibrotic, including HGF, (46,47) occludin (OCLN), (48) and GDF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(43) The implication of adipocyte-related pathways in the putatively pro-fibrotic myeloid cluster (Fig. 3E) may also be of interest: fat and fibroblasts/fibrosis are increasingly understood to have an intimate relationship; (40,44,45) lipid dysregulation is common at insulin injection sites and often co-occurs with fibrosis;(4-6) and we have previously postulated that, given current knowledge about the relationship between mechanical forces and adipocytes, tension offloading could be beneficial for both fibrosis and lipodystrophy in the setting of insulin use. (2) Conversely, other cell crosstalk pathways enriched in PP skin have been implicated by other studies as involved in tissue repair and/or possibly anti-fibrotic, including HGF, (46,47) occludin (OCLN), (48) and GDF.…”
Section: Discussionmentioning
confidence: 99%
“…To address this question, we employed a human foreskin xenograft model, which we have previously validated and used to study the effects of potential anti-fibrotic interventions. (36,40) We engrafted human foreskin samples onto the dorsum of immune-deficient mice (CD-1 nude -to prevent graft rejection), as previously reported, (36) then subjected xenografts to repeated injections of bleomycin with or without adjunct injections of recombinant IL4 protein; other grafts were made and not injected with bleomycin, as an UW/non-fibrotic control (Fig. 4A-B).…”
Section: Recombinant Il4 Reduces Bleomycin-induced Fibrosis In a Huma...mentioning
confidence: 99%
“…Emerging evidence in a rigorous study from the Longaker group show that mechanical cues are sufficient for this transition in mouse and human adipocytes. They found Piezo‐1/2 stretch channels in vivo are required for this transition during wound healing and promotes diminished scarring/regenerative healing in skin 148 . They also demonstrate that a subpopulation of dermal adipocytes can convert and clonally expand to profibrotic fibroblasts.…”
Section: Lipid Depletionmentioning
confidence: 93%
“…Adipocyte to fibroblast lineage transition can be tracked faithfully by inducible genetic lineage tracing in mouse skin, determined by the reduced expression of adipocyte marker Perilipin 1 (Plin1) and increased expression of alpha‐SMA (Acta2). Furthermore, lineage traced mature adipocytes can undergo dramatic morphological changes towards a dermal fibroblast phenotype 64,88,148 . The Rinkevich lab has challenged the conversion of lineage traced mature dermal adipocyte to profibrotic fibroblast at a functional level.…”
Section: Lipid Depletionmentioning
confidence: 99%
“…For wound healing, the mechanical sensing mediated by Piezo1 drives the transformation of fat cells into fibroblasts that form scars, thereby promoting wound fibrosis. Inhibiting Piezo1, in turn, could target the transformation of fat cells into fibroblasts to prevent and reduce scarring ( Griffin et al, 2023 ). Recent studies have also found that Piezo1 channels play an important role in pain perception.…”
Section: Basic Information On Piezo1mentioning
confidence: 99%